ANALISIS DAMPAK KENAIKAN TARIF PAJAK PERTAMBAHAN NILAI (PPN) TERHADAP MASYARAKAT DAN INFLASI DI INDONESIA - Hikmayani Subur; Wahyu Muh Syata (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to analyze the impact of increasing value added tax (VAT) rates on society and inflation in Indonesia. The method used is a literature review with a library study approach, utilizing secondary data sources such as books, articles, scientific works, previous research and other related literature. The research results show that the increase in the VAT rate from 10% to 11% and the planned increase to 12% in 2025 have caused various responses among the consumer community, the business community, the macro economy and towards inflation. That this increase will increase the expenditure burden, resulting in an increase in the prices of goods and services, as producers or service providers will most likely adjust their prices to cover the additional VAT costs they have to pay to the government. However, based on the law on harmonization of tax regulations, there are certain criteria regarding goods and services that are subject to VAT. This increase also aims to increase state revenue, expand the tax revenue base, reduce the state budget deficit, and maintain long-term fiscal stability. The increase in VAT from 10% to 11% has a direct impact on inflation with a contribution of around 0.4–0.5%. However, this impact tends to be short-term because it is limited to the initial adjustment phase. The impact on inflation tends to be limited, because the main factor for inflation in Indonesia is more influenced by global commodity prices, namely the sharp increase in commodity prices such as cooking oil and fuel oil (BBM). The government seeks to maintain price stability through a policy of sending taxes on essential goods and subsidies, so that the impact on society can be minimized.